Information formation in the computer system of acoustic properties of materials measurement - Бабак, В. П.; Филоненко, С. Ф.; Кришан, М. (Proceedings of National Aviation University (archive), 1999)
Considered is the structure and work of information formation device while measuring the acoustic properties of materials with the use of personal computer